2010
DOI: 10.1007/s10103-010-0787-8
|View full text |Cite
|
Sign up to set email alerts
|

Photodynamic efficacy of hypericin targeted by two delivery techniques to hepatocellular carcinoma cells

Abstract: The photocytotoxic effect of hypericin (Hyp) targeted by two different delivery techniques, namely, liposomes and anti-hepatocyte specific antigen (anti-HSA) was investigated. Optical absorption and steady-state fluorescence were used to analyze the conjugation of Hyp with anti-HSA model and to evaluate the encapsulation capacity and drug release in a liposome model. Particle size and thermal analysis of the prepared liposomes were performed using laser-light scattering and differential scanning calorimetry (D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…The cytocidal effect of PDT on hepatocellular carcinoma (HCC) has been examined in vitro and in vivo in original English articles since 1997 [24][25][26][27][28][29][30][31][32][33]. In the clinically accepted PS worldwide, PDT using 5-ALA showed cytocidal molecular responses in an HCC cell line according to Abo's report [24].…”
Section: Pdt For Primary Liver Malignanciesmentioning
confidence: 99%
“…The cytocidal effect of PDT on hepatocellular carcinoma (HCC) has been examined in vitro and in vivo in original English articles since 1997 [24][25][26][27][28][29][30][31][32][33]. In the clinically accepted PS worldwide, PDT using 5-ALA showed cytocidal molecular responses in an HCC cell line according to Abo's report [24].…”
Section: Pdt For Primary Liver Malignanciesmentioning
confidence: 99%
“…as photosensitizer for the photodynamic therapy of cancer by mean its single oxygen production, or it can be used for the photo-diagnosis of early epithelial cancer by taking advantage of its specific accumulation in various types of tumor cells (Kah et al, 2008;Ritz et al, 2008). Among different targets, tumor melanocytes (Hadjur et al, 1996), glioma cells (Huntosova et al, 2012), isolated crayfish neuron (Uzdensky et al, 2003) and hepatocellular carcinoma cells (Fadel et al, 2010) were quoted and reported as cell models for the study of the photodynamic efficacy of hypericin after photoirradiation.…”
Section: Features Of Hypericinmentioning
confidence: 99%
“…43−46 Moreover, encapsulation increased the photostability of hypericin, and in some cases, this encapsulation led to a decrease in its phototoxicity. 43,47 For these reasons, we investigated the phototoxicity and PDT efficacy of the newly constructed nanoparticles in vitro and in vivo.…”
Section: Introductionmentioning
confidence: 99%